Nilai-Nilai yang Dirasakan Pengguna Iphone Dalam Mempengaruhi Customer Loyalty Melalui Customer Saticfaction - Ida Bagus Nyoman Udayana; M. Rasyid Ridho (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Customer loyalty is very important for the company. A customer who buys regularly and repeatedly is said to be loyal. This definition places loyalty as a commitment. In this study the impact on brand image and customer satisfaction on customer loyalty. Customer values ​​that exist in iPhone products affect customer satisfaction which results in customers being loyal to iPhone. The population in this study is iphone customers who make purchases at least once. The number of samples used were 46 respondents, the sampling technique was distributing questionnaires using google form via Whatsapp. The author conducted research on the iPhone smartphone as the object of this research. The objectives of this study are (1) hedonic value has an effect on customer satisfaction, (2) social value has an effect on customer satisfaction, (3) functional value has an effect on customer satisfaction and (4) customer satisfaction has an effect on customer loyalty. The research findings show that customer expectations, more precisely the hedonic value on the iPhone brand, are valid and significant to customer satisfaction and customer loyalty. Social value is also valid and significant to customer satisfaction. Functional value is also valid and significant to customer satisfaction, and customer satisfaction has a positive effect on repurchase intention and customer loyalty. Therefore, iPhone companies must maintain credibility so that customers always trust and continue to use iPhone as the best brand for the smartphone level. The iPhone must also maintain brand awareness so that it is always remembered and used as the flagship smartphone in Indonesia. Keywords: hedonic value, social value, functional value, customer satisfaction, customer loyalty, iphone.